Deactivation of a Cobalt Catalyst for Water Reduction through Valence Tautomerism. Issue 39 (22nd May 2017) - Baydoun, Habib; Mazumder, Shivnath; Schlegel, H. Bernhard; Verani, Cláudio N.
Abstract: The activity of the water reduction catalyst [Co III (L 1 )(pyr)2 ]PF6 (1 ), where (L 1 ) 2− is a bis‐amido pyridine ligand and pyr is pyrrolidine, is investigated. Catalyst1 has an overpotential of 0.54 V and a high observed TOF of 23 min −1, albeit for a relatively short time. Considering the significant activity of1 and aiming to improve catalyst design, a detailed structural and electronic study is performed to understand the mechanisms of deactivation. Experimental and theoretical evidence support that the metal‐reduced [Co I (L 1 )] − is in tautomeric equilibrium with the ligand‐reduced [Co II (L 1 . )] − species. While [Co I (L 1 )] − favors formation of a Co III −H − relevant for catalysis, the [Co II (L 1 . )] − species leads to ligand protonation, structural distortions, and, ultimatley, catalyst deactivation. Abstract : Deactivate : A new Co‐based water reduction catalyst displays a high TOF of 23 min −1, albeit for a relatively short time. A detailed structural and electronic study was performed to understand the mechanisms of deactivation and conclude that tautomeric equilibrium between [Co I (L 1 )] − and [Co II (L 1 . )] − takes place. While the [Co I (L 1 )] − state supports catalysis through Co III ‐H − formation, the [Co II (L 1 . )] − state leads to catalyst deactivation. This knowledge is instrumental for the future design of robust catalysts.